Pengaruh Literasi Keuangan Dan Kepribadian Wirausaha Terhadap Kinerja Manajerial pada UMKM Di Sukarara Lombok Tengah - Saupiati, Intan artika; Indriani, Eni (Jurnal Riset Mahasiswa Akuntansi, 2025)
This study aims to analyze the influence of financial literacy and entrepreneurial personality on the managerial performance of MSME actors in Sukarara Village, Central Lombok. A quantitative approach was employed using multiple linear regression analysis. The sample consisted of 32 MSME actors selected through purposive sampling. The results indicate that partially, financial literacy has a positive and significant effect on managerial performance, while entrepreneurial personality shows no significant effect. Simultaneously, both variables do not significantly affect managerial performance, with an adjusted R² of 9.5%. This suggests that other factors play a more dominant role in influencing managerial performance. The study recommends continuous improvement in financial literacy and a holistic approach including external variables such as market access and technology to comprehensively enhance MSME managerial performance.